2017
DOI: 10.1101/gad.293704.116
|View full text |Cite
|
Sign up to set email alerts
|

Sorting out adipocyte precursors and their role in physiology and disease

Abstract: The ability to maintain and expand the pool of adipocytes in adults is integral to the regulation of energy balance, tissue/stem cell homeostasis, and disease pathogenesis. For decades, our knowledge of adipocyte precursors has relied on cellular models. The identity of native adipocyte precursors has remained unclear. Recent studies have identified distinct adipocyte precursor populations that are physiologically regulated and contribute to the development, maintenance, and expansion of adipocyte pools in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 109 publications
2
87
0
4
Order By: Relevance
“…Strikingly, the GFP + de-differentiated adipocytes have very low expression of the common adipocyte markers adiponectin ( Adipoq ), fatty acid binding protein 4 ( Fabp4 ), peroxisome proliferator activated receptor gamma γ ( Pparg ), resistin ( Retn ) and angiotensinogen ( Agt ), similarly to GFP- cells (Figure 4D). Meanwhile, these GFP+ cells have regained expression of common preadipocyte markers, such as Pdgfra , Pdgfrb , lymphocyte antigen 6 complex, locus A ( Ly6a ), Cd34, and fibronectin receptor beta subunit ( Itgb1 ) (Figure 4E) (Hepler et al, 2017; Wang and Seale, 2016). These de-differentiated adipocytes also increased expressions of some common fibroblast markers, such as Vimentin ( Vim ), Collagen Type I Alpha 1 Chain ( Col1a1 ), Smooth Muscle α Actin ( Acta2 ), and fibroblast activation protein ( Fap ), again, similarly to GFP- cells (Figure 4F).…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly, the GFP + de-differentiated adipocytes have very low expression of the common adipocyte markers adiponectin ( Adipoq ), fatty acid binding protein 4 ( Fabp4 ), peroxisome proliferator activated receptor gamma γ ( Pparg ), resistin ( Retn ) and angiotensinogen ( Agt ), similarly to GFP- cells (Figure 4D). Meanwhile, these GFP+ cells have regained expression of common preadipocyte markers, such as Pdgfra , Pdgfrb , lymphocyte antigen 6 complex, locus A ( Ly6a ), Cd34, and fibronectin receptor beta subunit ( Itgb1 ) (Figure 4E) (Hepler et al, 2017; Wang and Seale, 2016). These de-differentiated adipocytes also increased expressions of some common fibroblast markers, such as Vimentin ( Vim ), Collagen Type I Alpha 1 Chain ( Col1a1 ), Smooth Muscle α Actin ( Acta2 ), and fibroblast activation protein ( Fap ), again, similarly to GFP- cells (Figure 4F).…”
Section: Resultsmentioning
confidence: 99%
“…For simplicity, we have separated the factors that are likely to influence adipose morphology into two categories: (1) factors that regulate adipocyte number and (2) factors that regulate adipocyte size. As the regulation of adipocyte number (adipogenesis) is a well-studied subject with many in-depth reviews (Berry et al, 2016Hepler et al, 2017), we will focus on mechanisms that are hypothesized to regulate adipocyte size. Surprisingly, relatively few studies have identified cellular mechanisms that regulate adipocyte size.…”
Section: Cellular Mechanisms Hypothesized To Regulate Adipose Morphologymentioning
confidence: 99%
“…Считается, что эстрогены стимулируют липолиз через активацию гормон-чувствительной липазы и снижают липогенез за счет угнетения активности липопротеинлипазы [22]. Эстрадиол также повышает пролиферацию предшественников адипоцитов [23], и способствует ограничению накопления жира. Закономерно, что повышение концентрации эстрогенов сопряжено со снижением потребления пищи и уменьшением массы тела у женщин [13].…”
Section: мужчиныunclassified
“…Следствием этих событий является не только развитие адипонекроза, но и повышение экспрессии HIF-1α [37]. Преадипоциты и макрофаги в ЖТ также реагируют на гипоксию [23]. Как оказалось, усиленное накопление липидов в ВЖТ сопровождается развитием фиброза и воспаления, выраженность которого коррелирует с метаболическим синдромом [29,31].…”
Section: примечания: * жк -жирные кислоты жт -жировая ткань м -мужчunclassified
See 1 more Smart Citation